CIS impacts on farmer wellbeing in Senegal: evidence and opportunities - Hansen, James; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate information services (CIS) enable farmers and pastoralists to better understand, anticipate and manage climate risks. At a national level, Senegal’s foundation for CIS is among the strongest in West Africa. Yet the potential contribution of CIS to the wellbeing of the country’s farmers and agropastoralists remains underexploited and inequitably distributed. Impediments include economic and gender-based disparities, inadequate integration of climate information into agricultural advisories, weak capacity to communicate and interpret probabilistic information at a climate time scale, and lack of climate knowledge among agricultural professionals who support farmers and agropastoralists with information and advisories. This InfoNote summarizes available evidence of the use and impact of CIS for Senegal’s farmers, and discusses what AICCRA is doing to alleviate impediments and enhance the benefits of CIS to Senegal’s farming population.